M-Government as Solutions forE-Government problems in Indonesia - Ahmad Cucus; Marzuki Marzuki; Agus Sukoco; Maria Shusanti Febrianti (International Conference on Engineering and Technology Development (ICETD), 2012)
e-Government implementation has not been fully e-government in our country, its scale is still in its most basic level is the level of information, while the second level was already in. (interaction) have not been able to function properly. so that the goals expected by the government has not yet reached maximum.Some of the factors that lead to less maximal application of e-Government can be enhanced by m-Government, one of the things that makes the implementation of m-Government can develop the infrastructure that is better able to reach by the public both in terms of cost and knowledge